Genetic Twin Studies of Epilepsy Syndromes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The genetics of epilepsy syndromes was studied by an evaluation of 253 twin pairs at the University of Melbourne, Australia.